Tuning the electronic and structural properties of cerium oxide nanoparticles for the H2 production photocatalytic reaction - Thill, Alisson Steffli (2018)
The photocatalytic water splitting reaction showed to be a promising process to obtain renewable and clean energy, but the efficiency reached in this process is still low and must be improved to be viable. Considering this, the research on improving the efficiency of photocatalysts has attracted a strong interest in the past last years. Cerium oxide (CeO2−, 0 < x < 0.5) is a material recently investigated as a possible photocatalyst to obtain H2 from H2O. In this work, cerium oxide nanoparticles with high surface area (104 < S < 201 m2/g), high pore volume (32 < V < 132 mm3/g) values, wide range of diameter (2 < d < 90 nm) and O vacancies population (0.05 < x < 0.46) were applied to the H2 production photocatalytic reaction. The nanoparticles presented activity of up to 10 times higher than the commercial cerium oxide standard. UV-Vis, X-ray Diffraction, X-ray Absorption Spectroscopy, X-ray Photoelectron Spectroscopy, Ultraviolet Photoelectron Spectroscopy and Fourier Transform Infrared measurements were performed aiming to elucidate these results and to determine the main structural and electronic properties that can improve the H2 production photocatalytic reaction. It was obtained that the band gap energy depends on the nanoparticle synthesized and can be as low as 2.73 eV. The Ce 4f orbital occupation and the structural disorder presented by the nanoparticles is directly related with the band gap energies obtained. Density Functional Theory (DFT) calculations were performed to obtain the relation between the band structure (DOS) and the O vacancy population in order to explain the dependence of the band gap energy with the Ce 4f orbital occupation. Moreover, the O vacancies population at the surface have a very different effect depending on the presence or absence of mesopores, where a lower O vacancy population at the surface is better (worse) to the photocatalytic activity in the presence (absence) of mesopores. Furthermore O vacancies population at the surface plays a more fundamental role on the photocatalytic activity than the band gap energies for the samples presenting mesopores. The results allowed shedding light on the improvement of the properties of cerium oxide nanoparticles applied to optimize the H2 production photocatalytic activity.